Ідіопатична низкорослість: клініко-діагностичні критерії - Большова, О. В.; Самсон, О. Я.; Спринчук, Н. А.; Музь, В. А.; Ткачова, Т. О.; Антропова, О. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
This article focuses on current diagnostic criteria and clinical features patients with idiopathic short stature (ISS). According our data, part of such patients is 26.6% among patients with growth retardation referred to paediatric endocrinologist. We studied 41 cases of ISS (58.5% males). Familial history have 65.8% patients. Children have normal birth length and weight; without severe somatic, endocrine or genetic abnormalities. Patients showed height's delay from minus1.5 to minus 3.5 SD. Decreased of growth velocity accompanied with delay of the timing of puberty, negative adverse psychological and educational consequences. Pubertal patients showed higher levels of internalizing behaviour, lower levels of externalizing behaviour and selfesteem. Bone age delay was not more than 3 years in 90.24% children. GH peak >10 ng/ml was seen in 46.34% patients during two tests (with insulin and clonidin) and in 53.65% patients during one of the tests. IGF-1 levels were within the normal range. Children with idiopathic short stature may have some degree of GH insensitivity in IGF-I-producing tissue. Assessment of psychological status should be included in future research and in the current clinical care of patients with ISS.